2022
DOI: 10.37817/ikra-ithabdimas.v5i3.2228
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Meningkatkan Loyalitas Pelanggan Melalui Konsep Pemasaran Berdasarkan Nilai

Abstract: Pelaksanaan Pengabdian kepada Masyarakat ini bertujuan memperkenalkan konsep pemasaran yang berorientasi pada peningkatan nilai pada setiap produk yang ditujukan kepada konsumen. Ditengah kondisi Pandemi Covid-19 saat ini dimana daya beli masyarakat menurun, banyak masyarakat yang terkena PHK dan kemudian menekuni usaha sendiri, adanya kemudahan pemasaran digital membuat banyak sekali bermunculan pengusahapengusaha baru. Banyaknya pengusaha baru yang bersaing ketat dengan pengusaha yang sudah ada ditambah adan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of this study are in accordance with research showing (Utama & Murti, 2022;Alfia, 2022;Lukiyana & Nurudin, 2023). content marketing influence on thrifting purchase decisions, it can be concluded that the first hypothesis (h1) is accepted.…”
Section: Structural Model Testsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are in accordance with research showing (Utama & Murti, 2022;Alfia, 2022;Lukiyana & Nurudin, 2023). content marketing influence on thrifting purchase decisions, it can be concluded that the first hypothesis (h1) is accepted.…”
Section: Structural Model Testsupporting
confidence: 92%
“…Product Excellent for thrifting purchase decisions decides about what is offered to customers, so the superiority of the product makes the product have advantages and value in the eyes of customers so that it encourages them to buy it (Utama & Murti, 2022). Product Excellent can be defined as a product that has advantages and has various advantages when compared to competing products which will help strengthen the share of these brands and products (Alfia, 2022).…”
Section: Effect Of Product Excellent On Thrifting Purchase Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sistem barter menuntut kita untuk saling bertukar barang dengan nilai yang sama dengan barang yang akan kita diterima. Dapat dikatakan bahwa nilai pelanggan merupakan pertukaran antara manfaat dalam suatu produk maupun jasa dengan pengorbanan yang telah kita keluarkan untuk mendapatkan barang dan manfaat dari barang /jasa tersebut (Utama & Murti, 2022).…”
unclassified